PERSEPSI PESERTA DIDIK TENTANG PELAKSANAAN LAYANAN INFORMASI BIDANG PENGEMBANGAN KARIER DI KELAS XI SMA N 2 BAYANG - Karlina, Lina; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
Based on phenomenon that researchers found in the field with three counselors during the program guidance and counseling has not been effective in the absence of BK hours. So that, researcher raised issues about: how the perception of the students about implementation of information service on career development at XI SMA N 2 Bayang. This study aimed to describe the studentâs perceptions about the implementation of information services on career development about: 1) Implementation 2) advantages 3) Selection of materials 4) Methods and 5) Media of information service on career development provided by the counselor. This research was a descriptive research. The population was whole class XI SMA N 2, the total was 200 people. The samples were drawn from a population that numbered 50 people, therefore the technique used was: proportional random sampling, to take the data used was a questionnaire, while the technique analyzed using percentages. Results of this research revealed that the perception of the students about the implementation of information services on career development at class XI SMA N 2 Bayang about: 1) Implementation was in criteria pretty good. 2) Advantages was in criteria pretty good. 3) material selection was in pretty good criteria. 4) The service method was in pretty well criteria. 5) The media was in criteria pretty well.